Exploring the Mediating Role of Supply Chain Flexibility and Supply Chain Agility between Supplier Partnership, Customer Relationship Management and Competitive Advantage - Chairit Thongrawd; Sumalee Ramanust; Prasittichai Narakorn; Tummatinna Seesupan (International Journal of Supply Chain Management, 2020)
The key challenge of today’s global marketplace is to respond to the competitive challenges and to develop along with to sustain the competitive advantage for the organization. This paper examines that how partnership of suppliers and customer relationship management affects competitive advantage. Moreover, mediating effect of supply chain flexibility, supply chain agility is being examined as well. The data for current research was collected from the customers of textile firms of Indonesia. For this reason, a structured questionnaire was formed by adapting items form past studies. For data analysis, Smart PLS 3.0 and Statistical Package for Social Sciences (SPSS) version 23 were used. The Partial Least Square Structural Equation Modeling (PLS-SEM) is a relatively new technique and a second-generation SEM which works well for models which consist of multiple latent variables and series of cause-and-effect associations. The research findings show that supply chain flexibility is not proven a significant mediator between suppliers’ performance and competitive advantage. Also, the association between supply chain flexibility and competitive advantage is proven insignificant. As well, supplier partnership and supply chain agility association are also proven insignificant. All the other proposed hypotheses are proved to show significant relationships.